2020
DOI: 10.3389/fphys.2020.585765
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training on Gait, Balance, and Physical Fitness Asymmetries in Persons With Chronic Neurological Conditions: A Systematic Review of Randomized Controlled Trials

Abstract: Background: Persons with chronic neurological conditions (CNCs) often present with asymmetrical impairments, creating significant differences between contralateral limbs in body functions. These asymmetries have been associated with reduced mobility and balance, and are often targeted for reduction during rehabilitation. Exercise training has established benefits for persons with CNCs, and may have positive effects on asymmetry outcomes. Objectives: The purpose of this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…While confirming that MS differentially alters most aspects of lower limb motor functionality, the findings of the present study also suggest that the asymmetries of spatio-temporal parameters reported by many studies on gait of pwMS are likely to reflect the combined effect of muscular and joint kinematics asymmetries. In such a context, the use of waveformbased methods to assess interlimb (and possibly interlimb) symmetry may provide useful insights not only to better understand the impairments in motor control associated with the presence of MS, but also to accurately assess the effect of physical therapy and exercise training programs, which have been shown to have a positive effect on gait and balance asymmetries of individuals with MS as well as other chronic neurologic conditions [58]. However, future studies (possible longitudinal) are necessary to clarify the evolution of asymmetry during the disease progression, to identify specific peculiarities associated with MS type and with the sex of the affected individual and to assess the effects of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…While confirming that MS differentially alters most aspects of lower limb motor functionality, the findings of the present study also suggest that the asymmetries of spatio-temporal parameters reported by many studies on gait of pwMS are likely to reflect the combined effect of muscular and joint kinematics asymmetries. In such a context, the use of waveformbased methods to assess interlimb (and possibly interlimb) symmetry may provide useful insights not only to better understand the impairments in motor control associated with the presence of MS, but also to accurately assess the effect of physical therapy and exercise training programs, which have been shown to have a positive effect on gait and balance asymmetries of individuals with MS as well as other chronic neurologic conditions [58]. However, future studies (possible longitudinal) are necessary to clarify the evolution of asymmetry during the disease progression, to identify specific peculiarities associated with MS type and with the sex of the affected individual and to assess the effects of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various forms of PA willingly undertaken by the elderly are still being sought, as they are known to improve their overall functional efficiency, including body balance. Previous studies demonstrated positive effects of various forms of physical training on the gait and body balance [15][16][17]. One of the frequently examined forms of physical activity is Nordic Walking (NW).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated positive effects of various forms of physical training on the gait and body balance [ 15 , 16 , 17 ]. One of the frequently examined forms of physical activity is Nordic Walking (NW).…”
Section: Introductionmentioning
confidence: 99%
“…Another urgent investigation, which should be further explored, is optimal and safe exercise prescription (e.g., training intensity and duration) ( Farrell et al, 2020 ; Luo et al, 2020 ). We used the definition of training intensity and duration in a review ( Antje et al, 2020 ) as a reference: (1) training intensity (high: five times per week vs. moderate: 2–3 times per week), (2) training duration (short: 2–3 weeks vs. long: 4–8 weeks).…”
Section: Introductionmentioning
confidence: 99%